2009
DOI: 10.7202/602083ar
|View full text |Cite
|
Sign up to set email alerts
|

Est-il rationnel d’avoir des anticipations rationnelles?

Abstract: RÉSUMÉL’hypothèse d’anticipations rationnelles n’est elle-même rationnelle, en tant que processus mental de divination, que si elle est une stratégie dominante dans l’espace des stratégies. Cela suppose des hypothèses complémentaires : la rationalité individuelle doit être connaissance commune (collective) et le modèle de référence doit être « favorable ». On illustre ce point à l’aide du modèle de Muth. On appelle fortement rationnel un équilibre où l’hypothèse des anticipatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Despite the burgeoning literature on learning in macroeconomics, nobody seems to be able to produce a model with a plausible learning process that would converge to rational expectations equilibrium. A different approach is that taken by Guesnerie (1992), who took a more extreme position than Muth and the opposite of that which I propose, and suggested that agents might, by reasoning in a fully game-theoretic way, coordinate on rational expectations equilibrium. This eductive approach seems, in a macroeconomic context, to be a heroic assumption.…”
Section: Rational Expectationsmentioning
confidence: 85%
“…Despite the burgeoning literature on learning in macroeconomics, nobody seems to be able to produce a model with a plausible learning process that would converge to rational expectations equilibrium. A different approach is that taken by Guesnerie (1992), who took a more extreme position than Muth and the opposite of that which I propose, and suggested that agents might, by reasoning in a fully game-theoretic way, coordinate on rational expectations equilibrium. This eductive approach seems, in a macroeconomic context, to be a heroic assumption.…”
Section: Rational Expectationsmentioning
confidence: 85%